PEMBERDAYAAN MASYARAKAT MISKIN MELALUI INOVASI PROGRAM EKONOMI PRODUKTIF OLEH BAZNAS KOTA KOTAMOBAGU - Hasan, Faradila; Thomas, Freli (PERADA, 2023)
This research aims to analyze the effectiveness of BAZNAS Kotamobagu City's productive economic empowerment program in improving the welfare of poor community groups. This qualitative research with a case study design uses primary data from in-depth interviews and secondary data from regulatory reviews and literature. The results show that the skills training program and provision of business capital by BAZNAS Kotamobagu City positively impact the financial independence of several poor families in the region. However, evaluating the program implementation also identified several substantial remaining challenges. First, the beneficiary selection process is still considered too bureaucratic and potentially subjective. Second, the low awareness of some communities in carrying out their zakat obligations so that the realization of zakat fund raising is relatively low. Therefore, it is recommended to improve the beneficiary selection system by utilizing data digitization to improve efficiency and validity. The principles of accountability, transparency and objectivity in the selection process by zakat managers also need to be upheld. On the other hand, it is necessary to intensify massive public socialization and education related to the urgency of paying zakat as well as the real impact of zakat on economic empowerment programs for the poor. Increasing this literacy is important to optimize the potential for collecting zakat funds in the region. With these improvements, the BAZNAS Kotamobagu City productive economic empowerment program model has the potential to be replicated and make a significant contribution to the national mission to alleviate poverty in Indonesia.